2016
DOI: 10.5586/mb.2016.001
|View full text |Cite
|
Sign up to set email alerts
|

The genus Asteromella (Fungi: Ascomycota) in Poland

Abstract: Edited with financial assistance of the Polish Ministry of Science and Higher Education. This PDF has been certified using digital signature with a trusted timestamp to assure its origin and integrity. A verification trust dialog appears on the PDF document when it is opened in a compatible PDF reader. Certificate properties provide further details such as certification time and a signing reason in case any alterations made to the final content. If the certificate is missing or invalid it is recommended to ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…The asexual genus Asteromella was previously included in Dothideomycetes genera incertae sedis by Wijayawardene et al (2014) and Ruszkiewicz-Michalska (2016). The sexual morph of Asteromella was assigned to Mycosphaerella sensu lato (Crous et al 2007, Ruszkiewicz-Michalska 2016. However, Videira et al (2017) reported that Mycosphaerella sensu stricto has Ramularia asexual morphs.…”
Section: Dothideomycetes Oe Erikss and Winkamentioning
confidence: 99%
“…The asexual genus Asteromella was previously included in Dothideomycetes genera incertae sedis by Wijayawardene et al (2014) and Ruszkiewicz-Michalska (2016). The sexual morph of Asteromella was assigned to Mycosphaerella sensu lato (Crous et al 2007, Ruszkiewicz-Michalska 2016. However, Videira et al (2017) reported that Mycosphaerella sensu stricto has Ramularia asexual morphs.…”
Section: Dothideomycetes Oe Erikss and Winkamentioning
confidence: 99%